2023
DOI: 10.3389/feart.2022.1094880
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical reactions altering the mineralogical and multiscale pore characteristics of uranium-bearing reservoirs during CO2 + O2in situ leaching

Abstract: CO2 + O2in situ leaching has been extensively applied in uranium recovery in sandstone-type uranium deposits of China. The geochemical processes impact and constrain the leaching reaction and leaching solution migration; thus, it is necessary to study the CO2 + O2–water–rock geochemical reaction process and its influence on the physical properties of uranium-bearing reservoirs. In this work, a CO2 + O2–water–rock geochemical reaction simulation experiment was carried out, and the mineralogical and multiscale p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Reservoir stimulation can be roughly divided into chemical transformation and physical transformation. Chemical transformation refers to the use of injected solutions to react with the reservoir to increase its permeability. , This process is limited by the mineral composition of the reservoir when it is applied on-site. On the other hand, physical stimulation involves applying pressure to induce damage and fractures in the reservoir, thereby increasing its permeability .…”
Section: Introductionmentioning
confidence: 99%
“…Reservoir stimulation can be roughly divided into chemical transformation and physical transformation. Chemical transformation refers to the use of injected solutions to react with the reservoir to increase its permeability. , This process is limited by the mineral composition of the reservoir when it is applied on-site. On the other hand, physical stimulation involves applying pressure to induce damage and fractures in the reservoir, thereby increasing its permeability .…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of supply and demand of natural uranium is seriously unbalanced, and the dependence on imports remains high [ 2 , 3 ]. Therefore, there is an urgent need to increase the production capacity of natural uranium and the self-sufficiency rate of uranium resources, aiming to ensure energy security and accelerate the construction of a nuclear industry powerhouse [ 4 , 5 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…The cementation effect generated by Ca 2+ inhibits the dissolution of calcareous cement and clay mineral production in the soil [23], raising the charge on the soil surface and the ion exchange between Na + , K + , and solution Ca 2+ [24], thus increasing the interparticle affinities and the tight conjunction of particles that induce smaller soil pores, tighter particles, and stabler soil structures. Wang et al showed that during the leaching process, complex chemical reactions occur, causing changes in the pore structure within the ore body [25][26][27]. Hu et al found that the electrostatic repulsive force is affected by various factors, including the type of electrolyte, concentration, pH, and others [28,29].…”
Section: Introductionmentioning
confidence: 99%